Fatores que influenciam a percepção de autoeficácia financeira da investidora brasileira - uma perspectiva geracional - Salles, Elaine Fantini (2021)
The literature devoted to studies of investor behavior shows that men and women behave differently in this field. In general, women invest less, have a lower level of financial education and are more risk-averse. More recent studies also reveal that women's belief in their own ability to achieve financial goals is lower. As a way of contributing to this academic aspect, this dissertation investigates which factors influence the female investor's perception of financial self-efficacy and to which extent the financial knowledge and the generational factor are relevant variables in this relationship. To this end, a quantitative survey was carried out through an online questionnaire, with 37 questions, which obtained the participation of 1392 women, between January 11 and February 12, 2021. Financial self-efficacy was measured using the Lown scale (2011), while financial knowledge was measured using the scale created by Knoll and Houts (2012). Specific questions of interest to the author were also designed to relate them to the investor's perception of self-efficacy. Statistical analyzes were performed using the IBM SPSS Statistics® 20.0 and Stata® 15.0 software. The main results suggest a positive and significant relationship between financial knowledge and perception of financial self-efficacy, regardless of their generational factor. And that women with superior financial knowledge and vaster perception of financial self-efficacy have a higher number of sophisticated assets in the investment portfolio, with younger investors choosing these assets more frequently. Income has a positive relationship to the capital invested. Moreover, for the studied sample, no evidence was found that the experience of an abusive relationship affects the relationship with the perception of financial self-efficacy.